(untitled) (Journal of the College of Basic Education, 2022)
Beauty cannot give up on technical innovation that varies by what the artist create to promote his artistic work. The study highlights on the aesthetic variables of the flashback scenes in television drama, which is divided into four chapters as follows: Chapter one (methodological framework) includes the problem of the study, which was drafted in the following question: (what are the aesthetic variables for the flashback scenes in TV drama?) The importance of research is that it highlights the aesthetic variables that operate efficiently and effectively in the flashback scene in TV drama. The aim of the research is to find out the aesthetic variables in flashback scenes of in TV drama, the limits of research have been defined by studying the aesthetic changes in the TV drama represented by the series (Forbidden Love), and the Chapter ends with identifying the terminology. The second chapter (the theoretical framework and previous studies) included two sections the first dealt with flashback in the TV drama, and the second with aesthetic variables in flashback scenes. The researcher reached out to indicators associated, the researcher did not find a study that dealt with the subject of the aesthetic variables in flashback scenes of in TV drama. The third chapter included (Research Procedures) related to the methodology of research, adopted descriptive and analytical approach, based on the theoretical framework indicators as the research tool, the sample was selected intentionality to commensurate, the scene adopted the unit to analyze the sample. Chapter four (sample analysis and discussion of results), the sample of research has been analyzed and the conclusions were stated such as: the use of different means of modern techniques in providing flashback scenes increased the tensile and thrill element. The researcher presented the recommendations and sugges